Improving Students’ Listening Skill Using English Pop Songs at SMA Negeri 3 Jeneponto - Fahira Anjani; Ahmad Talib; Chairil Anwar Korompot (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
The purpose of this study was to find out whether the use of English pop song improve the listening skill of the second year students at SMA Negeri 3 Jeneponto. The independent variable in this study was the use of English pop songs while the dependent variable is listening skill. The population in this research was the students of class XI at SMA Negeri 3 Jeneponto, while the sample was students of class XI MIA 1 consist of 19 students. The research data was obtained by giving a listening test in the form of pretest and post test. The data analysis technique was descriptive statistics and t-test. Based on the results of the analysis, the probability value = 0.001 was lower than the level of significance value = 0.05. It can be concluded that the use of English pop songs can improve the listening skills of the students class XI MIA 1 at SMA Negeri 3 Jeneponto.Keywords— Improving, Pop Song, Listening Skill.